Haromyia, a new genus of long-legged flies from Dominica (Diptera: Dolichopodidae) - Runyon, Justin B. (Zootaxa, 2015)
The new micro-dolichopodid genus Haromyia gen. nov. and the type species H. iviei sp. nov. are described from the island of Dominica in the Lesser Antilles. Males and females of Haromyia are distinguished by the large setae on a bulging clypeus, minute size, and wing veins that are nearly straight and evenly diverging from wing base. Haromyia does not fit readily into any contemporary dolichopodid subfamily, although it superficially resembles the Enliniinae and Achalcinae. Haromyia should be regarded as incertae sedis until the dolichopodid subfamilies can be refined, particularly to better incorporate the tropical diversity of this large family.